Competitive interspersed staminate flowers in females: A problem in hybrid seed production of castor: Competitive interspersed staminate flowers in females: A problem in hybrid seed production of castor - K BHAVYA,; YAMANURA,; N NETHRA,; R MOHAN KUMAR,; R L RAVIKUMAR,; R SIDDARAJU, (Journal of Oilseeds Research, 2023)
The in vitro pollen germination study was carried out by using pollens of six genotypes which included two popular hybrids, two female and two male parents viz, DCH-177, ICH-66, DPC-9, SKP-84, DCS-9 and ICS-164 to know the competitiveness of interspersed staminate flowers (ISF). The standardized medium containing 15% sucrose, 0.01% H3BO3, 0.3% Ca(NO3).4H2O, 0.0214% Mg (SO4) 7H2O and 0.01% KNO3 were used in the study. The results revealed that highest % of pollen germination observed with ISF pollens of female parents (DPC- 9: 57.35% and SKP- 84: 44.51%) in both the hybrids compared to their respective male parents (DCS-9: 47.24% and ICS-164: 27.27%). It indicated the importance of rouging of ISFs in order to maintain the high genetic purity in castor hybrid and parental seed production.